“PARA MÍ, APRENDER UNA LENGUA SIGNIFICA...” REPRESENTACIONES DE ALUMNOS UNIVERSITARIOS MEXICANOS ACERCA DE LENGUAS EXTRANJERAS - Groult Bois, Noëlle (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Beliefs have been studied in many different contexts because they underlie and influence our actions in every aspect of our lives. In this paper, we will present the results of two studies carried out at the Foreign Language Center of the National Autonomous University of Mexico, about the beliefs of Mexican university level students of French and English as foreign languages. More precisely, we intended to find out what the beliefs of the students were as far as the process of foreign language learning was concerned (eg. what they thought about personal factors, materials, activities, the teacher’s role, and/or self-assessment). We will explain the methodology we used and the selection of our sample. The results we arrived at show that Mexican students have fairly average beliefs.